Manajemen Pemerintahan Desa Ciangsana Dalam Meningkatkan Produktivitas BUMDes - Alifvia Putri Ramadhina; Evi Priyanti (Universitas Serang Raya, 2023)
Ciangsana Village government management of Village-Owned Enterprises (BUMDes) needs to be done well so that BUMDes management can contribute to PADes. Without government management in accordance with its functions, it can bring setbacks in village development including BUMDes productivity. The purpose of this study was to determine Ciangsana Village government management in improving BUMDes productivity. This research uses descriptive qualitative research methods. The data collection techniques used were interviewed, observation, and documentation. Researchers use the theory of government management by George R Terry which has four dimensions, namely: planning, organizing, actuating and controlling. Based on the results of the research, it was found that planning has not been effective and efficient because it has not led to significant changes in the community and the BUMDes itself. Organizing is good with clear management through solidarity and cooperation. The actuating of the Ciangsana Village government carried out for BUMDes has not contributed to the PADes. Controlling is quite good because there are advisors and supervisors. Thus, it can be concluded that the management of Ciangsana Village government in increasing the productivity of BUMDes has not been effective.